Clinical Presentation of Patients with Thyroid Cancer in Tertiary Level Hospitals (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Thyroid malignancy is the most common endocrine malignancy seen in clinical practice. Incidence of thyroid cancer varies worldwide from 0.5 to 10 per 1,00,000 populations annually. Exact incidence of thyroid cancer in Bangladesh is not known.Aim: To find out the clinical presentation of patient with thyroid cancer and identify the association between socio- demographic features and clinical presentation.Methods: This cross sectional study was conducted purposively among 246 thyroid cancer patients in two tertiary hospitals of Dhaka city from 01 July 2018 to 30 June 2019. Data were collected by face to face interview using semi-structured questionnaire and checklist and were  were analyzed by Statistical Package of Social Science v23.Results: Study revealed that mean±SD age of the respondent was 37.9±12.20years (range 14-70 years). Majority 74.4% of respondents was female, married 72%, housewife 61.4%, primary education 69.0% and mean±SD monthly family income was BDT 17,681±10,602. Approximately 82.9% of patients had papillary cancer and 17.1% had follicular cancer. Various clinical presentations included, neck swelling 91.5%, swollen lymph node 41.9%, pain 36.6%, dysphonia 57.3% and dysphagia 35.4%. Study revealed the significant association of clinical presentation with gender, education and occupation of the respondents (p